Implementasi Pendidikan Karakter Dalam Pembelajaran Matematika Yang Berorientasi Pada Nilai-Nilai Moral - Nurul Faizah; Putri Indah Febriani; Nadia Elga Saputri; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Student character education is an education system that aims to instill certain character values ​​in students in which there are components of knowledge, awareness or will, as well as actions to carry out these values, for this review, teachers are able to carry out quality learning in every learning activity is included in learning mathematics. Student character education can be developed in learning mathematics that is oriented towards moral values. This study aims to implement the role of character education in mathematics education that is oriented towards moral values. This study uses SLR (Systematic Literature Review) research, where the data source is obtained from existing articles published by OJS (Online Journal System). Articles obtained through Google searches were grouped and tabulated based on the similarity of results/conclusions in the article results. After being tabulated, further analysis was carried out and finally reduced and conclusions drawn. Based on research data, the results obtained regarding the implementation of character education in learning mathematics that are oriented to moral values ​​find that: increasing moral values, developing moral values ​​and creativity, building character, problem solving processes, arousing curiosity, mathematical developments, logical thinking, being able to improve learning achievement, character education improves student learning outcomes. Based on these findings, it is hoped that educators, especially mathematics teachers, will always implement character education in learning mathematics that is oriented towards moral values. Keywords: Implementation, Character Education, Moral Values, Learning Mathematics